Role of BK polyomavirus (BKV) and Torque teno virus (TTV) in liver transplant recipients with renal impairment. Issue 10 (October 2018) - Herrmann, Anke; Sandmann, Lisa; Adams, Ortwin; Herrmann, Dominik; Dirks, Miriam; Widera, Marek; Westhaus, Sandra; Kaiser, Rolf; di Cristanziano, Veronica; Manns, Michael P.; Korth, Johannes; Richter, Nico; et al.
Abstract : Purpose. : Renal impairment is a common complication after liver transplantation (LT). While BK polyomavirus (BKV) has been linked to renal failure in kidney transplant recipients, Torque teno virus (TTV) is a surrogate marker for immunosuppression that does not have a clear association with any human disease. The impact of BKV and TTV on renal impairment after LT is unknown. Methodology. : In this retrospective study, urine and serum samples from 136 liver transplant recipients were screened for BKV and TTV by quantitative PCR. In addition, serum was screened for BKV‐specific antibodies and the VP1 typing region was sequenced for BKV genotyping. All parameters were correlated with clinical data. Results/Key findings. : BK viruria was detected up to 21 years after transplantation in 16.9 % of cases. BK viraemia was detected in 8.7 % of patients with BK viruria up to 4 years after LT. BKV‐specific antibodies were detected in 93.6 % of all LT recipients and correlated with BKV viral load in urine. There was no correlation between renal impairment and the detection of BK DNA in urine (OR 0.983). TTV DNA was detected in 84.6 % of serum samples and in 66.6 % of urine samples. The TTV viral load in serum correlated with the BKV viral load but had no impact on renal impairment. Conclusion. : Our data indicate that the detection of BKV and TTV is not a risk factor for renal impairment after LT. A correlation of TTV and BKV viral load seems to be an indicator for the immune status of the host.